Pengaruh Pendekatan PMR Terhadap Kemampuan Komunikasi Matematika Di Kelas IV SDN 10 Sungai Sapih - Pratiwi, Ardianti; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
The purpose of this research is to see the effect of realistic mathematics education approach (RME) on the mathematical communication ability class student in SD Negeri 10 Sungai Sapih Kota Padang. This study uses quantitative approach in the form of quasi experiment, the nonequivalent control group design, simple random sampling technique, ie 31 students of experimental class and 30 students of control class. The result of the research shows that the experimental class students use pmr approach which is higher than the control class without using the pmr approach. In hypothesis testing the results obtained by using T-Test obtained t count of tcount 3,48  > ttable  2,001 at the level of significance 0.05. Keywords: